Affective labor and alt-ac careers - Bessette, Lee Skallerup, 1977- (Lawrence, Kansas : University Press of Kansas, 2022)
"In her groundbreaking work The Managed Heart: Commercialization of Human Feeling (1983), the sociologist Arlie Russell Hochschild described "emotional labor management" as follows: "to induce or suppress feeling in order to sustain the outward countenance that produces the proper state of mind in others." An example would be someone working in customer relations, who must keep calm and be pleasant even when dealing with someone who is irate. While scholars like Sarah Ahmed and bell hooks have explored the affective realm when it comes to teaching and being a professor, there is less about the experience of those working in non-teaching areas of academia-"alt-ac." The purpose of this volume is to allow an opportunity for those in alt-ac careers to examine and share their affective experiences in their roles in technology, administration, research, and academic support services and as librarians, academic advisors, and writing center instructors-among others"--
Includes bibliographical references and index.
Keywords: College administrators -- Psychology -- United States; Teacher-administrator relationships -- United States; Emotions -- Social aspects; Work -- Psychological aspects; Motivation in education; Affective education